The Effects of Extra-Team Goal Disclosure on Team Performance, Viability, and Satisfaction - Sackett, Esther; Fitzsimons, Gráinne M. (Frontiers in Psychology, 2021)
In addition to the team's shared goals, team members also often hold goals unrelated to the team. Research about such goals, which we call "extra-team goals" (ETGs), has been limited.In the current research, we examine how awareness of a team member's ETGs affects team outcomes. A laboratory experiment examines the effects of disclosure of different types of ETGs by one team member (target) on team performance, team viability, and team satisfaction while engaging in a brainstorming task. Our findings suggest that there are significant positive effects of ETG disclosure on team performance, team viability, and team satisfaction, and that these effects are mediated by perceptions of the target's commitment to the team's goal.